Shade tree species matter: sustainable cocoa-agroforestry management - Asitoakor, B.K.; Rabild, A.; Vaast, P.; Ravn, H.P.; Owusu, K.; Mensah, E.O.; Asare, R. (Palgrave Macmillan, 2024)
Shade trees are important components of cocoa-agroforestry systems because they influence yields, soil fertility and the occurrence of pests and diseases and may support adaptation to climate change. Based on a review of the existing literature and on primary data from field experiments, this chapter reports on the species-specific effects of shade trees in relation to the management of insect pests, black pod diseases and their impacts on cocoa yield. Shade tree species in cocoa systems impact soil available phosphorus differently and shade tree species such as Spanish cedar (Cedrela odorata), limba (Terminalia superba)and mahogany (Khaya ivorensis) increase cocoa yield compared with cocoa systems without shade trees. The architecture of shade tree species may influence below-canopy temperatures and relative humidity, which poten-tially affect pests such as mirids and black pod disease infections and ultimately cocoa yield. As farmers have local knowledge of and prefer-ences for certain shade tree species, strengthening the combination of scientific and local knowledge can prove a powerful tool for the improved management of shade tree species, as well as cocoa pests and diseases.